PENERAPAN KERTAS KERJA PEMERIKSAAN (KKP) ATLAS DALAM PROSES AUDIT LAPORAN KEUANGAN - Vica, Monica; Budiwitjaksono, Gideon Setyo (Media Mahardhika, 2025)
The development of information technology in the field of auditing has presented various innovations that can improve the efficiency and effectiveness of the audit process. One of these innovations is the ATLAS (Audit Tool and Linked Archive System) application which is used to manage audit working papers digitally. This study aims to analyze the application of ATLAS audit working papers in the financial statement audit process based on the internship experience of Dony Firliawan's Public Accounting Firm (KAP). This study uses a qualitative approach through structured interviews and direct observation. The results of the study indicate that the application of ATLAS not only improves audit time efficiency but also maintains data integrity by ensuring that data remains accurate, complete, and consistent. From a business strategy perspective, ATLAS contributes to improving the quality of accuracy to clients and the profitability of public accounting firms.